2022
DOI: 10.1177/13623613221111207
|View full text |Cite
|
Sign up to set email alerts
|

Mental representations of speech and musical pitch contours reveal a diversity of profiles in autism spectrum disorder

Abstract: As an information-bearing auditory attribute of sound, pitch plays a crucial role in the perception of speech and music. Studies examining pitch processing in autism spectrum disorder have produced equivocal results. To understand this discrepancy from a mechanistic perspective, we used a novel data-driven method, the reverse-correlation paradigm, to explore whether the equivocal findings in autism spectrum disorder have high-level origins in top–down comparisons of internal mental representations of pitch con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…In this respect, atypically enhanced sensitivity to pitch and absolute pitch may be a by-product of atypical perception in autism. A recent study found greater variability in pitch perception in autistic individuals than in neurotypicals, and exceptional pitch sensitivity in a subgroup of autistic individuals ( Wang et al, 2023 ). Also observed and likely to occur is the combination of heightened visual perception and language delay as visual modality is also crucial for language acquisition.…”
Section: Discussionmentioning
confidence: 96%
“…In this respect, atypically enhanced sensitivity to pitch and absolute pitch may be a by-product of atypical perception in autism. A recent study found greater variability in pitch perception in autistic individuals than in neurotypicals, and exceptional pitch sensitivity in a subgroup of autistic individuals ( Wang et al, 2023 ). Also observed and likely to occur is the combination of heightened visual perception and language delay as visual modality is also crucial for language acquisition.…”
Section: Discussionmentioning
confidence: 96%
“…In the music domain, autism has been associated with typical or extraordinary musical skills, including perception of pitch, melody, and musical emotions (Chen et al, 2022;Janzen & Thaut, 2018;O'Connor, 2012;Ouimet et al, 2012;Quintin, 2019;Wang, Ong, et al, 2023), as well as enculturation to the pitch structure of Western music (DePape et al, 2012). However, reduced performance was also observed in pitch, emotion, and melodic processing (Bhatara et al, 2010;Ong et al, 2023;Sota et al, 2018), beat synchronization (Kasten et al, 2023;Morimoto et al, 2018;Vishne et al, 2021), active rhythmic engagement (Steinberg et al, 2021), and metrical enculturation in autism (DePape et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, from a more collective point of view, cultural attributes can be highlighted by agglomerating individual CIs, as well as intercultural differences (for instance, concerning the perception of face emotions [4]). Third, perception discrepancies between healthy individuals and mentally disordered or pathological individuals (e.g., speech and music perception with autistic vs. non-autistic individuals [5]) may be studied. Finally, to enhance computer-to-human or distant human-to-human interactions, it is possible to make one's signal (human or machine) consistent with the CI extracted from the other one, as suggested in [6], where authors set up a reusable audio filter as CI, embedding acoustic properties of honesty or certainty in speech.…”
Section: Introductionmentioning
confidence: 99%